Association between the prevalence of hyperuricemia and reproductive hormones in polycystic ovary syndrome - Mu, Liangshan; Pan, Jiexue; Yang, Lili; Chen, Qianqian; Chen, Ya; Teng, Yili; Wang, Peiyu; Tang, Rong; Huang, Xuefeng; Chen, Xia; Yang, Haiyan (Reproductive biology and endocrinology, 2018)
The prevalecne of hyperuricemia in polycystic ovary syndrome (PCOS) is still uncertain. We aimed to investigate the prevalence of hyperuricemia in PCOS and to determine the influence of reproductive hormones on uric acid concentration. This retrospective cross-sectional study was performed at a large reproductive medicine center. Between March 2007 and October 2016, a total of 1,183 women with PCOS and 10,772 women without PCOS were included. PCOS was diagnosed according to the Rotterdam criteria. Anthropometric parameters, blood pressure, uric acid, reproductive hormones, glucose and lipids were measured in all subjects. The serum uric acid (SUA) level was higher in women with PCOS than in women without PCOS. The prevalence of hyperuricemia in women with PCOS (25.48%) was significantly higher than that in women without PCOS (8.74%). Analysis stratified for age and body mass index (BMI) showed that both the SUA level and the prevalence of hyperuricemia were higher in women with PCOS of different age and BMI groups than in women without PCOS. After adjusting for age, BMI and estimated glomerular filtration rate (eGFR), logistic regression analysis revealed that the luteinizing/follicle-stimulating hormone (LH/FSH) ratio (odds ratio (OR) = 1.20, 95% CI = 1.01-1.43) and testosterone level (OR = 1.56, 95% CI = 1.27-1.90) were positively associated with the prevalence of hyperuricemia in females with PCOS. The serum uric acid (SUA) level and the prevalence of hyperuricemia markedly increased in women with PCOS. The testosterone level was positively associated with the SUA level and the prevalence of hyperuricemia in females with PCOS.